363 Neonatal morbidity, mortality and health outcomes in term infants born with arterial cord pH 7.0–7.1: a retrospective cohort study. (17th August 2022) - Crosby, Laura; McMahon, Susannah; Boxall, Kelly; Shiner, Alice; Scatchard, Rebecca; Yasin, Samra; Aga, Zaman; Bates, Sarah
Abstract : Aims: It is widely evidenced that neonates born with a cord pH <7.0 are at increased risk of adverse neurological outcomes. Neonates born with cord pH 7.26-7.31 have the lowest risk of such outcomes; the 'ideal pH'. There is little research on outcomes of neonates born with a cord pH of 7.0-7.1. As such, we aimed to compare short- and long-term outcomes between term neonates born with cord pH 7.0-7.1 and neonates born with the 'ideal pH'. Methods: A retrospective cohort study was completed on neonates born at the Great Western Hospital between 01/01/2016 and 31/12/2017 (N=8994, after exclusion criteria N=8383). Neonates were split into the exposure group (pH 7.0-7.1) and control group (pH 7.26-7.31). 175 infants were randomly chosen from each group. Demographics of infants in each group are described in table 1 . Short- and long-term outcomes ( table 2 ) were collected by retrospective review of the medical records. For every outcome, the risk ratio, 95% confidence intervals and P values were calculated, with P≤0.05 deemed statistically significant. Results: Neonates born with a cord pH 7.0-7.1 have increased risk of: 1 minute Apgar score <7.0 (P=0.000003) NICU admission (P=0.0042) Respiratory morbidity in those admitted to NICU (P=0.0098) Requiring resuscitation at birth (P=0.000004) Presenting to PAU/ED with an infection within 3 years (P=0.004) Neonates born with a cord pH of 7.26-7.31 were more likely to: Present to PAU/ED (P=0.05) Present to PAU/ED with a neurological problem within 3 years (P=0.04) There was no significant difference between groups in: Duration of NICU stay Inpatient stays or outpatient referrals 3 year mortality Conclusion: Our study suggests that neonates with cord pH 7.0-7.1 are more likely to require initial resuscitation, NICU admission and respiratory support, but that there is no increase in mortality. Cord pH therefore has the potential to prognosticate short-term morbidity. The increase in neurological presentations in infants with pH 7.26-7.31 is unexpected. Our study is limited by several factors including but not limited to: the small sample size, single centre data collection with unknown loss to follow up, and demographic differences between exposure and control group.